Printable liquid metal ink and preparation method thereof

By adding p-aniline derivatives and nanocil to the liquid metal ink for ultrasonic modification, a printable liquid metal ink was prepared, which solved the problem of the oxide layer hindering conductivity, and achieved a flexible electrode with high conductivity and adhesion, suitable for biosensing applications.

CN116694141BActive Publication Date: 2025-03-04THE CHINESE UNIV OF HONG KONG (SHENZHEN)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310774259.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-03-04
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

The existing liquid metal inks have problems in flexible electrode printing and other surface printing that the oxide layer hinders conductivity and stretchability, and is difficult to completely remove, limiting its application in biosensing.

Method used

A printable liquid metal ink was prepared by incubating the gallium indium alloy in hydrochloric acid, adding p-aniline derivatives and nanoclays for ultrasonic modification, forming liquid metal nanoparticles and mixing them with polyethylene copolymers.

Benefits of technology

This method effectively inhibits the formation of oxide layers, improves the conductivity and adhesion of liquid metal ink, can form flexible electrodes with high conductivity, and print them on different flexible substrates, with good water stability and storage, and is suitable for biosensing applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116694141B_ABST
    Figure CN116694141B_ABST
Patent Text Reader

Abstract

The present invention discloses a printable liquid metal ink and a preparation method thereof, the preparation method comprising the following steps: 1) taking a gallium-indium alloy and placing it in a relatively high concentration of hydrochloric acid, ensuring that the hydrochloric acid can completely cover the gallium-indium alloy, and incubating overnight; 2) washing with anhydrous ethanol, washing three times to ensure that the hydrochloric acid is completely removed, adding a para-aniline derivative and nano-clay, and mixing until dissolved; 3) using an ultrasonic cell disruptor for ultrasonic modification; 4) washing the liquid metal nanoparticles obtained in step 3) with water; 5) dissolving a polyethylene copolymer in water; 6) resuspending the liquid metal particles in step 4) with deionized water, and then mixing with the ink carrier obtained in step 4) to obtain liquid metal ink. The present invention adopts a physical-chemical combination method for compound modification, and the obtained liquid metal ink has high viscosity and strong adhesion after mixing with the ink carrier, and can effectively adhere to a flexible substrate to form a conductive electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional materials, and in particular to a printable liquid metal ink and a preparation method thereof. Background Art

[0002] Liquid metal is a new type of conductive ink, which usually refers to a low-melting alloy with a melting point below 200°C. Liquid metal has a low melting point at room temperature and is liquid at room temperature. Compared with traditional fluids, liquid metal has excellent thermal conductivity and electrical conductivity, and a wide liquid phase temperature range, so it is increasingly being studied. Room temperature liquid pure metals existing in nature include mercury, cesium, strontium and gallium, with melting points of -38.87°C, 28.65°C, 27°C and 29.8°C, respectively. Among them, mercury is relatively volatile, mercury and amalgam have certain toxicity, and mercury-containing residues enter the ecological cycle, which will cause harm to humans and the environment, so they should be used with caution. Cesium is an active alkali metal. Cesium is easily oxidized in the air and reacts violently with water. Strontium is also an active metal that can react directly with water and react violently with acid. At the same time, strontium is an unstable radioactive element.

[0003] Liquid metal ink can be used to print on different surfaces and is also one of the main raw materials that affect the electrical properties of flexible electrodes. However, due to the high surface tension of liquid metal, it cannot be directly used for printing flexible electrodes or printing on the surface, which limits its application in biosensing. At present, the more common treatment is to reduce the surface tension of gallium-indium alloy (melting point is lower than room temperature, it is the most commonly used conductive ink) and make it printable through physical methods such as ultrasound or mechanical stirring. However, during the ultrasonic treatment, since liquid metal is also easy to oxidize, the oxide on the liquid metal block breaks, and a new oxide layer is formed on the liquid metal nanoparticles, which hinders the recombination of liquid metal, resulting in the oxide layer formed on the liquid metal being less conductive and stretchable than the liquid metal itself. Secondly, the oxide layer (Ga2O3) is also easy to react with water to form rod-shaped crystals (GaOOH), further reducing the performance of the material. Therefore, in order to improve the performance of liquid metal ink applied to flexible electrode printing or other surface printing, the growth of oxides should be suppressed. Therefore, liquid metal needs a simple and feasible method to reduce the impact of oxides on its conductivity and can be easily printed.

[0004] The current method for oxide suppression and functionalization of liquid metal droplets is chemical modification. The thickness of the oxide layer is reduced to 30% by modification of thiolate molecules, and then a layer of LM droplets is deposited on the flexible substrate and made conductive by subsequent sintering treatment. However, since the insulating Ga2O3 oxide layer is continuously formed on the surface of the liquid metal particles, even after the solvent is completely volatilized, the circuit without sintering is basically composed of a large number of liquid metal particles piled together and insulated from each other, where the liquid metal particles are encapsulated in the Ga2O3 oxide layer, and the oxide layer is difficult to remove by simple sintering. At the same time, due to the low adhesion of liquid metal nanoparticles, they are easy to fall off after printing and sintering on flexible substrates or other surfaces.

[0005] Therefore, since the use of current physical and chemical methods still cannot completely eliminate the adverse effects of the Ga2O3 oxide layer, there are corresponding problems, which limits the application of liquid metal ink in flexible electrode printing or printing on other surfaces, and thus also limits its application in biosensing. Summary of the invention

[0006] In view of the problems existing in the existing liquid metal applications, the present invention provides a method for preparing a printable liquid metal ink, which can be used for printing flexible electrodes or printing on other surfaces.

[0007] The present invention provides a method for preparing liquid metal ink for printing flexible electrodes, comprising the following steps:

[0008] 1) taking an appropriate amount of gallium-indium alloy and placing it in hydrochloric acid, the hydrochloric acid covers the gallium-indium alloy, incubating overnight, removing the oxide layer, and obtaining a liquid metal solution;

[0009] 2) washing the liquid metal solution obtained in step 1) with anhydrous ethanol to remove hydrochloric acid, adding p-aniline derivatives and nanoclay, and mixing until dissolved to obtain a mixture;

[0010] 3) using an ultrasonic cell disruptor to perform ultrasonic modification on the mixture obtained in step 2) to obtain liquid metal nanoparticles;

[0011] 4) washing the liquid metal nanoparticles obtained in step 3) with water to completely remove the anhydrous ethanol and obtain a high-concentration liquid metal solution;

[0012] 5) dissolving the polyethylene copolymer in water to obtain an ink carrier;

[0013] 6) Using deionized water to resuspend the high-concentration liquid metal solution obtained in step 4), and then mixing it with the ink carrier obtained in step 5) to obtain liquid metal ink.

[0014] Furthermore, the working frequency of the ultrasonic modification in step 3) is 30%, the ultrasound is turned off for 2 seconds and on for 2 seconds in a cycle, and the reaction time is 90-120 minutes.

[0015] Furthermore, after adding the p-aniline derivative and nanoclay in step 2), the content of the gallium-indium alloy is 90-95wt%, the content of the p-aniline derivative is 4-9wt%, and the content of the nanoclay is 0-1wt%.

[0016] Furthermore, after adding the p-aniline derivative and nanoclay in step 2), the content of the gallium-indium alloy is 92-95wt%, the content of the p-aniline derivative is 7-9wt%, and the amount of the nanoclay is 0.5-1wt%.

[0017] Furthermore, the p-aniline derivative is any one or a combination of p-aminothiophenol (PATI), p-aminobenzoic acid (PABA), p-phenylenediamine (PPD) and p-bromophenol (PBA).

[0018] Furthermore, the concentration of hydrochloric acid in step 1) is 0.5M.

[0019] Furthermore, the polyethylene copolymer in step 5) is any one of polyvinyl alcohol, polyvinyl pyrrolidone and polyethylene imine.

[0020] The present invention also provides a printable liquid metal ink, which is prepared by the above-mentioned preparation method.

[0021] The present invention also provides a flexible wearable biosensor, which comprises the printable liquid metal ink.

[0022] The present invention also provides the use of the printable liquid metal ink as described above in printing on a functional surface, wherein the surface is any one of an electrode, a microfluidic channel, a hydrogel and glass.

[0023] The beneficial effects achieved by the technical solution of the present invention are:

[0024] 1. The present invention provides a method for preparing a printable liquid metal ink, which is based on a gallium-indium alloy-p-aniline derivative system. The raw materials mainly include gallium-indium alloy, p-aniline derivatives and nanoclay, and the composition is clear. The addition of p-aniline derivatives and nanoclay can inhibit the formation of an oxide layer during ultrasound and functionalize the liquid metal. The amount of addition is related to the degree of bonding of bonded alloy nanoparticles. The liquid metal modified with p-aminobenzoic acid has more carboxyl groups on its surface and can be further used as a sensing interface.

[0025] 2. The present invention adopts physical-chemical combined means to modify the compound. The obtained liquid metal ink has high viscosity and strong adhesion after mixing with the ink carrier. It has good wettability with other components and can effectively adhere to the flexible substrate to form a conductive electrode, or be used for printing on other surfaces. The prepared liquid metal ink can be used to print a liquid metal flexible electrode with high conductivity and wide applicability, which overcomes the problems in the prior art. The oxide layer can be removed after simple treatment, supports the connection of the circuit, and has good hydrophilicity. It can be printed on different flexible substrates and can also be printed on different surfaces. At the same time, the ink has good water stability and can be stored as powder for preservation. At the same time, due to the presence of functional functional groups (carboxyl, amino, hydroxyl, thiol, etc.) on the surface of the liquid metal ink, it can be further bonded with gold nanoparticles to support biosensor modification, so it has application potential in biosensing, and provides feasibility for 3D printing flexible wearable biosensors. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.

[0027] Figure 1 Macroscopic and microscopic morphology of the liquid metal ink prepared in Example 1;

[0028] Figure 2 Macroscopic and microscopic morphology images of the liquid metal ink prepared in Comparative Example 1;

[0029] Figure 3 The macroscopic morphology of the electrode printed with the liquid metal ink prepared in Example 1 before and after sintering and the microscopic morphology after sintering;

[0030] Figure 4 This is a particle size distribution diagram of the liquid metal ink prepared in Example 1;

[0031] Figure 5 This is a microscopic morphology of the freeze-dried liquid metal ink prepared in Example 1;

[0032] Figure 6 The conductivity test result of the freeze-dried liquid metal ink prepared in Example 1;

[0033] Figure 7 The adhesion test result of the liquid metal ink prepared in Example 1;

[0034] Figure 8Conductivity test results of liquid metal ink modified with different aniline derivatives. DETAILED DESCRIPTION

[0035] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The present invention is specifically introduced below in conjunction with the specific embodiments.

[0036] An embodiment of the present invention provides a method for preparing a printable liquid metal ink, comprising the following steps:

[0037] 1) Take an appropriate amount of gallium-indium alloy and place it in hydrochloric acid, ensuring that the hydrochloric acid can completely cover the gallium-indium alloy, incubate overnight to obtain a liquid metal solution. This step can remove the oxide layer;

[0038] 2) washing the liquid metal solution obtained in step 1) with anhydrous ethanol for 3 times to ensure that the hydrochloric acid is completely removed, adding the p-aniline derivative and the nanoclay, and mixing until dissolved to obtain a mixture;

[0039] 3) using an ultrasonic cell disruptor to perform ultrasonic modification on the mixture obtained in step 2) to obtain liquid metal nanoparticles;

[0040] 4) washing the liquid metal nanoparticles obtained in step 3) with water to completely remove the anhydrous ethanol and obtain a high-concentration liquid metal solution;

[0041] 5) dissolving the polyethylene copolymer in water to obtain an ink carrier;

[0042] 6) Using deionized water to resuspend the high-concentration liquid metal solution obtained in step 4), and then mixing it with the ink carrier obtained in step 5) to obtain liquid metal ink.

[0043] Specifically, the working frequency of the ultrasonic modification in step 3) is 30%, the ultrasound is turned off for 2 seconds and on for 2 seconds in a cycle, and the reaction time is 90-120 minutes.

[0044] Specifically, after adding the p-aniline derivative and nanoclay in step 2), the content of the gallium-indium alloy is 90-95wt%, the content of the p-aniline derivative is 4-9wt%, and the content of the nanoclay is 0-1wt%.

[0045] Preferably, after adding the p-aniline derivative and nanoclay in step 2), the content of the gallium-indium alloy is 90-95wt%, the content of the p-aniline derivative is 4-9wt%, and the amount of nanoclay added in step 2) is 0.5-1wt%.

[0046] Specifically, the p-aniline derivative is any one or a combination of p-aminothiophenol (PATI), p-aminobenzoic acid (PABA), p-phenylenediamine (PPD) and p-bromophenol (PBA).

[0047] Specifically, the concentration of hydrochloric acid in step 1) is 0.2-0.7M.

[0048] Preferably, the concentration of hydrochloric acid in step 1) is 0.5M.

[0049] Specifically, the polyethylene copolymer in step 5) is any one of polyvinyl alcohol, polyvinyl pyrrolidone and polyethylene imine.

[0050] An embodiment of the present invention further provides a printable liquid metal ink, wherein the liquid metal ink is prepared by the above-mentioned preparation method.

[0051] The embodiments of the present invention also provide the use of the printable liquid metal ink in the preparation of flexible wearable biosensors.

[0052] The embodiments of the present invention also provide the use of the printable liquid metal ink as described above in printing on functional surfaces, wherein the surface is an electrode, a microfluidic channel, a hydrogel, glass, etc.

[0053] Unless otherwise specified, the materials, reagents, etc. used in the following examples can be obtained from commercial sources. Unless otherwise specified, the detection methods used in the following examples are all experimental methods, detection methods and preparation methods disclosed in the field.

[0054] Example 1 Preparation and storage method of liquid metal ink

[0055] 1) Place the gallium-indium alloy in 0.5M hydrochloric acid, ensure that the hydrochloric acid can completely cover the gallium-indium alloy, incubate overnight, remove the oxide layer, and obtain a liquid metal solution;

[0056] 2) washing the liquid metal solution obtained in step 1) with anhydrous ethanol for three times to ensure that the hydrochloric acid is completely removed, adding p-aminobenzoic acid (PABA) and nanoclay, wherein the content of gallium-indium alloy is 92wt%, the content of p-aniline derivative is 7wt%, and the content of nanoclay is 1wt%, and mixing until dissolved to obtain a mixture;

[0057] 3) using an ultrasonic cell disruptor to perform ultrasonic modification on the mixture obtained in step 2), with an operating frequency of 30%, an ultrasonic off-for-2s cycle and an on-for-2s cycle, and a reaction time of 105 min, to obtain liquid metal nanoparticles;

[0058] 4) washing the liquid metal nanoparticles obtained in step 3) with water to completely remove the anhydrous ethanol and obtain a high-concentration liquid metal solution;

[0059] 5) dissolving polyvinyl pyrrolidone in water to obtain an ink carrier;

[0060] 6) resuspending the high-concentration liquid metal solution obtained in step 4) with deionized water, and then mixing it with the ink carrier obtained in step 5) to obtain liquid metal ink;

[0061] 7) After ultrasonic treatment, the liquid metal ink can be stored in anhydrous ethanol for subsequent sensor modification and standby use; or it can be pre-cooled and then freeze-dried at -80°C for 12 to 36 hours for long-term storage.

[0062] Comparative Example 1 Preparation of unmodified liquid metal ink

[0063] 1) Place the gallium-indium alloy in 0.5M hydrochloric acid, ensure that the hydrochloric acid can completely cover the gallium-indium alloy, incubate overnight, remove the oxide layer, and obtain a liquid metal solution;

[0064] 2) washing the liquid metal solution obtained in step 1) with anhydrous ethanol for three times to ensure that the hydrochloric acid is completely removed;

[0065] 3) using an ultrasonic cell disruptor to ultrasonically modify the liquid metal solution obtained in step 2), with an operating frequency of 30%, an ultrasound off for 2 seconds and an on for 2 seconds cycle, and a reaction time of 105 minutes to obtain liquid metal nanoparticles;

[0066] 4) The liquid metal nanoparticles obtained in step 3) are washed with water to completely remove the anhydrous ethanol to obtain a high-concentration liquid metal solution.

[0067] Use of Liquid Metal Ink

[0068] The liquid metal ink prepared in step 6) of Example 1 and the liquid metal ink prepared in Comparative Example 1 were photographed with a scanning electron microscope at the same angle and light, and their macroscopic morphologies were photographed. The results are shown in FIG. Figure 1 and Figure 2 ; Use the liquid metal ink prepared in step 6) of Example 1 to print electrodes on the surface of the nitrile flexible substrate, and rub to remove the oxide layer. Take a scanning electron microscope photo at the same angle and light to capture the macroscopic morphology of the electrode before and after sintering and the microscopic morphology after sintering. The results are shown in Figure 3 ,in Figure 3 The left picture shows the macroscopic morphology of the electrode before sintering, the middle picture shows the macroscopic morphology of the electrode after sintering, and the right picture shows the microscopic morphology of the electrode after sintering. Figure 1-3It can be seen that after removing the oxide layer, the electrode surface presents a certain metallic luster. The scanning electron microscope results show that the printed electrode microstructure is interconnected nanoparticles, and the particle size is relatively uniform. The particle size is calculated, and the results are shown in Figure 4 ,from Figure 4 It can be seen that the unmodified gallium-indium alloy prepared in Comparative Example 1 has a particle size of about 1000nm after ultrasound. The larger particle size is also the reason why it is easy to deposit. The particle size of the liquid metal particles modified with aniline derivatives is mainly concentrated at 300nm, which indicates that the modification of aniline derivatives effectively inhibits the formation of liquid metal oxide layer, resulting in a reduction in particle size.

[0069] The liquid ink prepared in step 6) of Example 1 and the freeze-dried liquid metal ink in step 7) of Example 1 were respectively photographed by scanning electron microscope after being left for one week. The results are shown in FIG. Figure 5 ,in Figure 5 The left picture is a scanning electron microscope image of the liquid ink prepared in step 6) of Example 1, and the right picture is a scanning electron microscope image of the freeze-dried liquid metal ink after being left for one week. Figure 5 It can be seen that after the freeze-dried liquid metal powder is placed for a week, its microscopic morphology is not significantly different from that of the electrode printed in ink form, and its particles are relatively uniform, indicating that the liquid metal ink can be stored as a powder for a long time.

[0070] The freeze-dried liquid metal ink powder in Example 1 (7) was redissolved in anhydrous ethanol and deionized water respectively to observe whether the conductive stability changed before and after storage. The results are shown in FIG. Figure 6 ,from Figure 6 It can be seen that the freeze-dried liquid metal ink powder shows similar conductivity to the liquid metal ink powder before freeze-drying in anhydrous ethanol and deionized water, and shows further improvement in conductivity in aqueous solution, which indicates that the performance of the liquid metal ink will not be greatly affected when it is stored as a powder. At the same time, the improvement in the conductivity of the aqueous solution provides a theoretical basis for this new type of liquid metal ink with water as the carrier.

[0071] Physical and chemical properties testing of liquid metal ink:

[0072] 1. Adhesion test:

[0073] The effect of the modified molecules on the contact angle was measured using a JC2000D1 contact angle meter (Powereach, Shanghai). 10 μL of the liquid ink prepared in step 6) of Example 1 and 10 μL of the unmodified liquid metal ink prepared in Comparative Example 1 were dispensed onto two glass slides; the slides were placed in an oven at 37°C for 10 minutes to ensure that the samples were completely dried and a thin film was formed on the slides; then, 2 μL of water was dropped onto the thin film using the instrument and the contact angle was collected. The results are shown in Figure 7 .from Figure 7 It can be seen that compared with the unmodified liquid metal ink prepared in Comparative Example 1, the contact angle of the liquid ink prepared in step 6) of Example 1 (contact angle is 24°) is reduced, that is, after modification of the aniline derivative, the liquid ink exhibits better adhesion.

[0074] 2. Conductivity detection:

[0075] Electrochemical measurements were performed under a CHI660E system (CH Instruments, Inc., Shanghai). The reference electrode was an Ag / AgCl electrode, the counter electrode was a Pt electrode, and the working electrode was a GC disk electrode with a diameter of 3 mm. The electrodes were continuously polished on a micro-pad (Buehler, Lake Bluff, IL) using an alumina slurry made of dried Buehler alumina and Milli-Q water. The electrodes were thoroughly rinsed with Milli-Q water and ultrasonically treated in Milli-Q water for 1 minute after polishing. All potentials were compared with a silver / silver chloride reference electrode at room temperature. PBS buffer containing 0.1M K3Fe(CN)6, 0.1M K4Fe(CN)6 and 0.1M KCl was used as the electrolyte solution for EIS measurements, and CV was scanned from -0.3V to 1.5V at room temperature. To prove its conductivity, the preparation was carried out according to the steps of Example 1, except that other p-aniline derivatives (p-aminothiophenol (PATI), p-phenylenediamine (PPD) and p-bromophenol (PBA)) were modified to prove their enhancement of the conductivity of liquid metal. The results are shown in Figure 8 .from Figure 8 It can be seen that after modification with different p-aniline derivatives, the liquid metal ink exhibits good conductivity, among which the PDD-modified liquid metal ink exhibits obvious conductivity enhancement.

[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a printable liquid metal ink, characterized in that: The following steps are involved: 1) placing a gallium-indium alloy in hydrochloric acid, covering the gallium-indium alloy with the hydrochloric acid, and incubating overnight to obtain a liquid metal solution; 2) washing the liquid metal solution obtained in step 1) with anhydrous ethanol, adding p-aniline derivatives and nanoclay, and mixing until dissolved to obtain a mixture, wherein the p-aniline derivative is any one or a combination of p-aminothiophenol, p-aminobenzoic acid, p-phenylenediamine and p-bromophenol; 3) using an ultrasonic cell disruptor to perform ultrasonic modification on the mixture obtained in step 2) to obtain liquid metal nanoparticles; 4) washing the liquid metal nanoparticles obtained in step 3) with water to obtain a high-concentration liquid metal solution; 5) dissolving the polyethylene copolymer in water to obtain an ink carrier; 6) Repeat step 4) to obtain a high concentration liquid metal solution using deionized water, and then mix it with the ink carrier obtained in step 5) to obtain liquid metal ink.

2. The method for preparing liquid metal ink according to claim 1, characterized in that: After the p-aniline derivative and nano-clay are added in step 2), the content of the gallium-indium alloy is 90-95wt%, the content of the p-aniline derivative is 4-9wt%, and the content of the nano-clay is 0.5-1wt%.

3. The method for preparing liquid metal ink according to claim 2, characterized in that: After the p-aniline derivative and nano-clay are added in step 2), the content of the gallium-indium alloy is 92-95wt%, the content of the p-aniline derivative is 7-9wt%, and the content of the nano-clay is 0.5-1wt%.

4. The method for preparing liquid metal ink according to claim 1, characterized in that: The concentration of hydrochloric acid in step 1) is 0.5M.

5. The method for preparing liquid metal ink according to claim 1, characterized in that: The polyethylene copolymer in step 5) is any one of polyvinyl alcohol, polyvinyl pyrrolidone and polyethylene imine.

6. A printable liquid metal ink, characterized in that: The liquid metal ink is prepared by the preparation method described in any one of claims 1-5.

7. A flexible wearable biosensor comprising the printable liquid metal ink as claimed in claim 6.

8. Use of the printable liquid metal ink in functional surface printing as claimed in claim 6, characterized in that: The surface is any one of an electrode, a microfluidic channel, a hydrogel and glass.

Citation Information

Patent Citations

  • Self-sintering liquid metal ink as well as preparation method and application thereof

    CN112538290A

  • Method of manufacturing non-sintered liquid metal ink

    US20230159771A1